RPE drift during cycling in 18ºC vs 30ºC wet bulb globe temperature - Green, J. M.; Pritchett, R. C.; Crews, T. R.; Tucker, D. C.; Mclester, J. R.; Wickwire, P. J. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: The potential influence of a hotter vs cooler environment on ratings of perceived exertion (RPE) estimations during longer duration exercise is not well-understood. This study compared overall and differentiated RPEs during cycling in 18°C vs 30ºC wet bulb globe temperature (WBGT). Methods: Male volunteers (n=16) completed a maximal cycling trial (60 rev·min-1, 25 Watts/min) to determine VO2 max and ventilatory threshold (VT) before completing 2 (counterbalanced) longer duration cycling trials. At 30ºC WBGT (30C) and 18ºC WBGT (18C), subjects cycled 60 min (60 rev/min, 90% individualized VT). Heart rate (HR, b/min) and rectal temperature (Tre, ºC) were recorded every 5 min with corresponding RPE-overall (RPE-O), RPE-legs (RPE-L) and RPE-chest (RPE-C) estimations. Results: HR was not significantly different at 5 min but was greater (P£0.05) for 30C at all other time points. During 30C, Tre was significantly greater (25, 30, 35, 40, 45, 50, 55 and 60 min), RPE-O was significantly greater (5, 40, 45, 50, 55 and 60 min), RPE-L was significantly greater (55 and 60 min) and RPE-C was significantly greater (35, 40, 45, 50, 55 and 60 min). Conclusion: Greater cardiovascular (HR) and thermal (Tre) strain partially explain greater perceptual ratings during 30C. Discernible RPE differences resulted mid-way through 60 min cycling with minimal differences initially. Results suggest RPEs are magnified in a 30ºC (vs 18ºC) environment beyond 30 min duration. Additionally, a 30ºC environment resulted in a less pronounced impact on RPE-L (vs RPE-C and RPE-O).